Prediksi Kesulitan Keuangan Dengan Menggunakan Model Altman Modifikasi Z-Score - Wahyuni, Sri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Textile industry is contracted due to the Covid-19 pandemic, reduction of export, increase of import, and the spread of thrifting trend. This unfavorable condition has put losses to the issuers of textile industry. Here financial distress prediction analysis is crucial since the earlier the financial distress is detected, the more useful information received by internal parties. Such information is used by the stakeholders as a consideration in their decision-making. The objective of this research is to identify and analyze the prediction of financial distress obtained from the use of the modified Altman Z”-Score. Using purposive sampling technique, twelve companies were selected as the sample of this quantitative descriptive study. The financial distress was measured using the modified Altman Z”-Score, which incorporates four financial ratios. This study finds that seven companies (58%) are predicted to have financial distress for three years, that two companies (17%) have fluctuating financial conditions, that two companies (17%) improves their financial performance and tat one company (8%) has good financial condition for three years. The results of this research are useful for investors as a signal for the consideration of investment decision-making and for companies as an early warning and early cues for evaluation to prevent bankruptcy. Abstrak Industri tekstil terkontraksi akibat pandemi Covid-19, penurunan ekspor tekstil, peningkatan impor produk tekstil serta maraknya trend thrifting yang mengakibatkan emiten tekstil mengalami kerugian. Analisis prediksi kesulitan keuangan penting karena semakin dini tanda kesulitan keuangan terdeteksi, maka akan semakin baik bagi pihak internal serta dapat memberikan informasi yang berguna sebagai sinyal bagi pemangku kepentingan untuk bahan pertimbangan dalam pengambilan keputusan. Penelitian ini bertujuan untuk mengetahui dan menganalisis prediksi kesulitan keuangan dengan menggunakan model Altman Modifikasi Z”-Score. Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan kuantitatif. Pemilihan sampel menggunakan teknik purposive sampling sehingga didapatkan sampel berjumlah 12 perusahaan. Kesulitan keuangan diukur dengan menggunakan model Altman Modifikasi Z